Corporate Tax Policy: Impact Tunnelling Incentive, Debt Covenant, And Transfer Pricing - Deden Tarmidi; Agustin Fadjarenie; Lin Oktris (Jurnal Akuntansi, 2023)
Transfer pricing is considered one of the corporate policies for minimizing the tax burden. This study aims to analyze the role of transfer pricing in the influence of tunnelling incentives and debt covenants on corporate tax policy. Manufacturing companies listed on the Indonesia Stock Exchange are unit analyses in this study. Their 398-panel data after purposive sampling. Using STATA, this study found that tunnelling incentives are used in transfer pricing activities, while debt covenant and transfer pricing are used in management in tax policies. Meanwhile, debt covenant is not widely used in the transfer pricing scheme, and tunnelling incentive also does not affect management on corporate tax policy. The mediating role of transfer pricing is not found in the indirect effect of tunnelling incentives and debt covenants on corporate tax policy. This result explains that transfer pricing and debt covenants are commonly used by companies in their tax policy.